I do not remember how to do the operations to solve these types of equations... x/-7 + 9 = 6 and the problem x/-4 + (-7) = (-16). what is the difference and how do you work them out?
how do I work out the problem x/-7 +9 = 6
First thing you do is take get everything on the opposite side of x. To do that, start by taking the parenthesis off first. Then take the (-7) and moving it over.
x/-4 + (-7) = (-16)
x/-4 - 7 = -16
x/-4 - 7 + 7 = -16 +7 Remember, whatever you do to one side, you have to do to the other.
x/-4 = -9 Now multiply both sides by -4
x= 36 Remember, the negatives cancel out
Now plug it back into the the original equation to see if it works.